1995
DOI: 10.1002/ijc.2910610221
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the inhibitory effect of the angiogenesis inhibitor, TNP‐470, and mitomycin c on the growth and liver metastasis of human colon cancer

Abstract: Angiogenesis inhibitors have attracted considerable interest. The anti-tumor and anti-metastatic effects of TNP-470, an angiogenesis inhibitor, and mitomycin C (MMC), a representative anti-neoplastic agent, were investigated using a xenotransplanted human colon cancer, TK-4. Suturing of small pieces of TK-4 tumors to the cecal wall in nude mice (orthotopic transplantation) induced liver metastasis. Mice were randomly divided into 3 groups; a control group given saline solution, a group receiving TNP-470 and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 10 publications
3
31
0
Order By: Relevance
“…Antiangiogenic therapy offers a number of potential benefits including lack of resistance to some agents, synergistic interaction to other modalities, lack of significant toxicity compared with conventional agents, and a potent antitumor effect. However, the anti-neoplastic actions and side effects of angiogenitic inhibitors and cytotoxic agents were clearly different [6,7,14] . Administration of angiogenesis inhibitors such as TNP-470 might keep the tumor and its metastases dormant (rather than killing it), and co-administration of cytotoxic drugs might kill it [5,8,21,22] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antiangiogenic therapy offers a number of potential benefits including lack of resistance to some agents, synergistic interaction to other modalities, lack of significant toxicity compared with conventional agents, and a potent antitumor effect. However, the anti-neoplastic actions and side effects of angiogenitic inhibitors and cytotoxic agents were clearly different [6,7,14] . Administration of angiogenesis inhibitors such as TNP-470 might keep the tumor and its metastases dormant (rather than killing it), and co-administration of cytotoxic drugs might kill it [5,8,21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Kato et al [23] reported significant effects of TNP-470 in combination with mitomycin-C, adriamycin, CDDP, and 5-FU in mouse models. The anti-tumor effect of TNP-470 was enhanced by combination chemotherapeutic agents [7,8,14,25,26] . Shishido et al [6] further showed that the effect of TNP-470 in combination with CDDP against pancreatic carcinomas was enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental protocol The tumor transplantation and evaluation methods have already been reported. 17) Briefly, small pieces of TK-13 tumor tissue (5 mm in diameter and about 100 mg in weight) were resected from subcutaneous tumors in the exponential growth phase, and the pieces were sutured to the wall of the cecum of nude mice with 6-0 Dexon (Davis-Geck, Manati, PR) after removal of the serosa. The mice were divided into 3 groups: a control group (n=17), a UFT group (n=18) and an S-1 group (n=17).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that tumor expansion with formation of new blood vessels are related to metastasis (Weidner et al, 1991;Weidner et al, 1993;Holash et al, 1999;Hood et al, 2002). Therefore, the use of angiogenic inhibitors in order to reduce tumor metastasis is a promising method for treating tumors (O'Reilly et al, 1994;Konno et al, 1995;Zetter, 1998;Ebos et al, 2009;Pàez-Ribes et al, 2009). Prostate cancer is related to angiogenesis and vascular invasion and thus inhibition of angiogenesis can be used as a method to treat prostate cancers (Weidner et al, 1993;Bagley et al, 2011;Gyftopoulos et al, 2011;Assadian et al, 2012;Lynch et al, 2012;Pande et al, 2012;Pinto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%